The effect of ions doping on the rheological properties of ferrite ferrofluids - Chen, Fang; Zhang, Jie; Liu, Xiaobing; Yan, Shengnan; Li, Wangxu; Yan, Zhaoqiang; Li, Zhenggui (Frontiers in Materials, 2023)
A series of ferrite nanoparticles were synthesized via ion doping and then were coated by surfactant and dispersed in perfluorinated polyether oil (PFPE-oil), respectively, and the various ferrite ferrofluids were obtained. The scanning electron microscope (SEM) was used to characterize the morphology of particles and disperse state of ferrofluid, energy-dispersive spectroscopy (EDS) was used to study the chemical composition of particles, fourier transform infrared spectroscopy (FTIR) and thermogravimetric analysis (TGA) were used to study the coated effect of PFPE-acids on particles, vibrating sample magnetometer (VSM) was used to research the magnetization curves of ferrite particles, and the rheological property of the ferrite ferrofluids were studied by a rheometer. The results show that Zn 2+ , Mn 2+ /Zn 2+ , and Dy 3+ ions were doped in the ferrite nanoparticles with size less than 50 nm. The four kinds of ferrite nanoparticles have the characteristics of super-paramagnetic materials, and the M-T curves decrease with increasing temperature, while, their decline rates are notably different. The ferrite particles are coated by PFPE-acids chemically and the ferrofluids have well dispersion stability. The rheological properties of the ferrite ferrofluids change with the variation of the ion doping, magnetic field strength, temperature, ect. The magnetism and viscosity of ferrite ferrofluids are regularly affected by the ion doping, and the results will have a great significant on the basic research and related applications.